Aplikasi Pengawasan Kendaraan di Daerah Perbatasan Entikong berbasis Teknologi PWA Dan Load Balancing Server - Ikhwan Ruslianto; Uray Ristian (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Entikong is one of Indonesia's border areas that is crossed by vehicles across national borders from Malaysia and Brunei. Data collection is based on computers to check passing vehicles. This is of course a problem if you want to get vehicle data quickly and effectively. This will cause problems again if there is interference on the internet or the internet condition becomes slow. Therefore, it is necessary to make a mechanism for accessing application pages with offline conditions. The application of Progressive Web Apps (PWA) in an application can keep the website accessible to users even though the internet condition is offline. Service Workers on PWA will work based on an internet connection. If the application is online, data will be called from the server to use. If offline, the data will be retrieved from the device cache sent to the application. From the test results, even though the internet is offline, the Sipintar application website can still be accessed. The browser storage required is only 630kb for cache storage, 2kb for Service Worker and 302b for Indexed DB. In addition, server load balancing is needed for the use of heavy network traffic. From the results of monitoring the server shows that the usage of bandwidth resources on the Sipintar application server only has a most usage of 1.3 Mbps.